2020
DOI: 10.1039/d0cc90422h
|View full text |Cite
|
Sign up to set email alerts
|

Correction: An ionic liquid-modified RGO/polyaniline composite for high-performance flexible all-solid-state supercapacitors

Abstract: Correction for ‘An ionic liquid-modified RGO/polyaniline composite for high-performance flexible all-solid-state supercapacitors’ by Chang Dong et al., Chem. Commun., 2020, DOI: 10.1039/d0cc04691d.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The specific capacitance (Cs) value for synthesized rGFP ternary composites is high (283.4 F/g) compared to GO (5.5 F/g), respectively, to the binary RGF (66.4 F/g) (Figure 10). When the EM was represented by RGO-ionic liquid/PANI (RGO-IL/PANI) [94], the reported capacitance was 193 F/g at 1 A/g due to RGO modification with ionic liquid, and a retention capacity of 87% after 2000 cycles at 5 A/g.…”
Section: Synthesis and Vibrational Properties Of Pani-rgo Composites ...mentioning
confidence: 99%
See 3 more Smart Citations
“…The specific capacitance (Cs) value for synthesized rGFP ternary composites is high (283.4 F/g) compared to GO (5.5 F/g), respectively, to the binary RGF (66.4 F/g) (Figure 10). When the EM was represented by RGO-ionic liquid/PANI (RGO-IL/PANI) [94], the reported capacitance was 193 F/g at 1 A/g due to RGO modification with ionic liquid, and a retention capacity of 87% after 2000 cycles at 5 A/g.…”
Section: Synthesis and Vibrational Properties Of Pani-rgo Composites ...mentioning
confidence: 99%
“…Recently, numerous studies have been reported on the use of CP-based composite materials, especially PANI and CNs of the type CNTs, graphene, and their derivatives or hybrids, resulted from the combination of the two, in a wide range of applications, in particular, as EMs in DSSCs [ 16 , 20 , 22 , 24 , 60 , 62 , 68 , 81 ] and supercapacitors [ 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 ]. In the composite configuration, the two components, i.e., CP and the carbon-based material, make their main contribution, the former through chemical stability, mechanical resistance, and redox behavior (PEDOT, PANI) and the latter through conductivity character and a high specific surface area.…”
Section: Synthesis and Vibrational Properties Of Cps-cns Composites A...mentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to the EDLCs, the PCs have higher specific capacitance and energy density due to their reversible redox process. In numerous PCs, conductive polymers (CPs) such as polyaniline (PANI) [ 23 ], polypyrrole (PPy) [ 24 ], polyinode (PIn) [ 25 ], and Poly(3,4-ethylenedioxythiophene) (PEDOT) [ 26 ], have been favored by researchers because of their good electrochemical performance, facile synthesis, and excellent environmental stability. Among them, the PPy with good conductivity and specific capacitance has been widely studied, which mainly focused on the modification of its micromorphology via template method, and combination with other materials, such as PPy/carbon nanotubes (CNTs) [ 27 , 28 ], PPy/graphene oxide (GO) [ 29 , 30 ], PPy/Ti 3 C 2 T x [ 31 , 32 ], PPy/MnO 2 [ 33 , 34 ], PPy/CuS [ 35 ], etc.…”
Section: Introductionmentioning
confidence: 99%